Tomas Ó Crohan’s Autobiography: A Cultural Analysis of Robin Flower’s English Translation - Lucchitti, Irene (ABEI Journal, 2003)
Tomás Ó Crohan’s autobiography, An tOileánach, was translated into English by Robin Flower, appearing as The Islandman in 1934. It has been widely read ever since, perhaps more widely than the Irish original. A view that something is lost in the translation has persisted through the years. This paper seeks to examine this view by considering Flower’s translation as both process and product and the context in which it was produced. It seeks also to consider what it was that Flower translated.